Penerapan Model Eliciting Activities Berbantuan Media APPEM Untuk Meningkat Kemampuan Pemahaman Konsep Pada Siswa SD - Bashrul Muna; Ratri Rahayu; Himmatul Ulya (Universitas Muria Kudus, 2019)
This research aimed to describe the improvement of the ability of mathematical concept comprehension, the improvement of students’ activity, and the improvement of the teacher’s teaching skill through the implementation of Model Eliciting Activities model by using APPEMmedia.This classroom action research is conducted on the fourth grade of SDN6Klumpit Gebog Kudus in the Academic Year 2018/2019 with the number of subject is 14 students and here the researcher as the teacher. This research is conducted in 2 cycles which consist of 3 meetings for each cycle.The result of the research showed that (1) the students’ ability of mathematical concept comprehension on cycle I got the classical mean score 67,14 as a inoughpredicate and it improved on cycle II to 83.10 as a good predicate, (2) the students’ activity on cycle I got the classical average 70,76 as a inoughpredicate and improved to 82,59 as a goodpredicate on cycle II, (3) the teacher’s teaching skill on cycle I got avrage the classical 2,89 as a good criteria and improved to 3,21 as a good criteria on cycle II. Based on the research result, it can be concluded that the implementation of Model Eliciting Activities by using APPEM media can improve the ability of mathematical concept comprehension, the students’ activity and the teacher’s teaching skill in organizing the learning activity